Typification of a Linnaean name in Gleicheniaceae (Polypodiopsida) - Lima, Lucas Vieira; Viveros, Raquel Stauffer; Salino, Alexandre (Phytotaxa, 2018)
Gleicheniaceae are an ancient fern family with about 157 species and six genera (PPG I 2016). Although its taxonomy has been through several changes in the last years (Gonzales & Kessler 2011), a great gap remains in both taxonomy and nomenclature. For the Neotropics, there are several national or regional taxonomic treatments of the family (e.g. Proctor 1985, Lellinger 1989, Tryon & Stolze 1989, Moran 1995, Mickel & Smith 2004, Kessler & Smith 2018) and a revision of the Neotropical members of the genus Sticherus Presl (1836: 51) (Gonzales & Kessler 2011), but only few of them are dedicated to solve nomenclatural issues.